2011
DOI: 10.1001/archinternmed.2011.330
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones in the Prevention of Menopausal Bone Loss and Menopausal Symptoms

Abstract: clinicaltrials.gov Identifier: NCT00076050.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 26 publications
5
109
1
6
Order By: Relevance
“…However, the outcomes of soy isoflavone treatment for the prevention of menopausal bone loss are conflicting. Although many researchers have shown that daily supplementation with soy isoflavones could prevent postmenopausal osteoporosis and improve bone strength, thus decreasing the risk of fracture in menopausal women (Wong et al, 2009;Taku et al, 2010Taku et al, , 2011, other studies have indicated that the daily administration of soy isoflavones could not prevent bone loss in menopausal women (Arjmandi et al, 2005;Levis et al, 2011). Equol is a metabolic end-product of soy isoflavones with high stability and a slow excretion speed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the outcomes of soy isoflavone treatment for the prevention of menopausal bone loss are conflicting. Although many researchers have shown that daily supplementation with soy isoflavones could prevent postmenopausal osteoporosis and improve bone strength, thus decreasing the risk of fracture in menopausal women (Wong et al, 2009;Taku et al, 2010Taku et al, , 2011, other studies have indicated that the daily administration of soy isoflavones could not prevent bone loss in menopausal women (Arjmandi et al, 2005;Levis et al, 2011). Equol is a metabolic end-product of soy isoflavones with high stability and a slow excretion speed.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 years, despite urine tests confirming that the women in the soy group had ingested nearly 20 times as much soy as those taking the placebo, there were no significant differences in bone density and no improvement regarding night sweats, insomnia, loss of libido, or vaginal dryness compared with the placebo group. There were few serious adverse effects in either group [42]. This study has been criticized for numerous study-design defects.…”
Section: Isoflavonoidsmentioning
confidence: 94%
“…One type of soybean known as black soybean, or seomoktae is traditionally used in Korea because its seed coat contains natural phenolic compounds (Zhao et al 2015). Seomoktae exerts protective effects against a number of disease such as cardiac diseases, metabolic syndromes, osteoporosis, and cancer (Levis et al 2011;Jung et al 2013). Seomoktae contains a high level of glutamine and asparagine residues, whose negatively charged carboxyl groups may bind calcium and, hense, may increase calcium bioavailability.…”
Section: Introductionmentioning
confidence: 99%